Improving clean and healthy Islamic educational institution - Artha, Ruly; Junaedi, Junaedi; Maseleno, Andino; Huda, Miftachul; Ibrahim, Mohd. Hairy (Linguistics and Culture Review, 2021)
Islamic educational institution was required to be clean, beautiful, comfortable, safe, and healthy. The facts showed that there were still many Madrasah Ibtidaiyah with low health degrees. The success of the creating such conditions depended on the quality of the program planning. The process of preparing the program included the analysis of situations which produced the information related to the planning, the existence of problem priority determination activities, and the preparation of program planning based on the chosen problems. The research objective was to analyze the implementation of clean and healthy school/madrasah program planning. several madrasah had not properly planned the clean and healthy madrasah program. It was recommended that the principal arranged planning by involving all elements of madrasah and cooperate with third parties, especially health universities.